An Econometric Model of the U.K. - Johnston, J. (Review of Economic Studies, 1961)
Journal Article An Econometric Model of the U.K. Get access J. Johnston J. Johnston Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 1, October 1961, Pages 29–39, https://doi.org/10.2307/2296179 Published: 01 October 1961